Development and characterization of a panel of anti-idiotype antibodies to 1C10 that cross-neutralize HIV-1 subtype B viruses - Kaku, Yu; Matsumoto, Kaho; Kuwata, Takeo; Zahid, Hasan Md; Biswas, Shashwata; Gorny, Miroslaw K.; Matsushita, Shuzo (Frontiers in Virology, 2022)
The V3 loop of the human immunodeficiency virus type 1 (HIV-1) envelope protein (Env) is one of the conserved immunogenic regions targeted by neutralizing antibodies (nAb). Two different binding modes of anti-V3 abs have been reported in studies using two V3 mimotopes: the ladle-type and cradle-type. We previously isolated a ladle-type nAb, 1C10, that potently and broadly neutralized clade B viruses. Despite its potent neutralization activity, 1C10 possesses no unique features in its amino acid sequence. We hypothesized that the neutralization potency of 1C10 is derived from its antigen-binding characteristics, which are not a consequence of the two previously reported binding modes of anti-V3 nAbs. To analyze epitope-paratope interactions between 1C10 and the V3 loop, we produced five anti-idiotypic antibodies (anti-Id abs) from mice immunized with 1C10 nAb. The idiotopes of the anti-Id Abs on the 1C10 heavy chain were estimated by alanine scanning, germline reversion mutagenesis, and a 1C10 sibling clone. Next-generation sequencing combined with homology modeling revealed contact between R315 at the tip of the V3 loop and 1C10 by D53 of CDRH2 and Phe/Asp of CDRH3. These amino acids were enriched in the anti-Id -ab-reactive B cell receptors encoded by the IGHV3-30 gene. We also found that 20% of HIV-infected individuals had abs specific to the anti-Id abs, as well as both of the V3 mimotopes, that did not respond to the linear V3 peptide. Our findings showed that the anti-Id abs induced by 1C10 recognized a key amino acid formation essential for steric interactions between the ladle-type nAb and the V3 loop. We also revealed the coexistence of anti-V3 ab reactivity to V3 loop mimotopes and to the anti-Id abs in HIV-positive individuals.